A study of tracheostomy in paediatric age group (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Tracheostomy refers to a surgical procedure of creation of a stoma at the skin surface that leads  into the tracheal lumen. In recent times tracheostomy is most commonly indicated in patients with prolong  intubation. The aim of this study was to establish data regarding indications, complications and techniques of  tracheostomy in paediatric age group.  Methods: A retrospective study was done in the patients who had undergone tracheostomy in VS Hospital  between age group of 1 month to 16 years. Conclusion: In terms of indications, decannulation and complications the procedure has become safe due to  having better equipment’s and facilities
Keywords: tracheostomy; paediatric; paediatric age group